THE STUDY OF COMPOSTING TIME PERIOD BY USING TOFU CESSPOOL ACTIVATOR’S AND FISH CESSPOOL ACTIVATOR’S - ENNI ROSIDA SINAGA; ROMUALDUS RONALD SIGA (JURNAL INFO KESEHATAN, 2014)
Tofu and fish cesspool has contained an organic substance for microorganism growth in decomposing process of organic substances. The purpose of this research was to know the ability of tofu cesspool activators and fish cesspool activators in composting process. The research type was pre-experiment research and used posttest only design. The independent variables are tofu cesspool activator and fish cesspool activator. Dependent variables are composting period time, temperature, pH, humidity, and C/N ratio. Data collected were measured result of parameter area, and laboratory test. The data was analyzed descriptively. Research result indicated that in tofu cesspool activator treatment got pH, 6,9, temperature was 34,7ᴼC, humidity was 64,9% RH and C/N ratio was 13,83% and needed 12 days composting. For group of fish cesspool activator treatment got pH 7, temperature was 35,4ᴼC, humidity was 66,8%RH and C/N ratio was 17,5% and needed 14 days composting. Based on some literatures descripted best temperature was 25ᴼC-60ᴼC, and best Ph about 6.5-7.5, optimum humidity 40-60% RH, period time of composting was 2-3 weeks, and C/N best ratio was 10-20%. Activator of tofu cesspool’s and fish cesspool’s can be used in composting process. It was suggested to community to use both activators in composting.